Damage propagation in complex biological systems following exposure to low doses of ionising radiation. (21st November 2007) - Feinendegen, Ludwig E.; Paretzke, Herwig G.; Neumann, Ronald D.
Biological organisms present hierarchical levels of organisation capable of maintaining homeostasis at low-level perturbations through intricate signalling between cells. Ionising radiation may damage DNA and other molecular components. This primary risk rises linearly with dose over a certain dose range. A second risk describes the probability of the initial DNA and other damage to propagate in the body to cause disease, such as cancer. The homeostatic control of the second risk does not function in a linear fashion. Moreover, low-dose irradiation may adaptively up-regulate protective responses at different organisational levels genetically controlled. Such adaptive protections (APs) usually defend also against the inevitable abundant non-radiogenic perturbations. Below ≅0.1Gy, APs are potentially beneficial in outweighing the consequences of the relatively rare radiogenic damage at low doses. The balance between health risk and benefit of low-level irradiation of an individual may become predictable by gene-expression profiles also for eventually treating disease.